Analyzing Congressional Research Service Reports on Education: How Is Information Used at Congress's Think Tank?. (August 2022) - Rubin, Paul G.; Ayscue, Jennifer B.; Uzzell, Elizabeth M.
The Congressional Research Service (CRS) is the nonpartisan research and analytical arm of the U.S. Congress and is physically and structurally located within the Library of Congress. Despite the role of CRS as a critical information provider and technical assistant to actors crafting and implementing federal policy, CRS reports, which serve as a key mechanism of information dissemination and influence by the organization, only became widely available to the public following the adoption of the Consolidated Appropriations Act of 2018. This study uses content analysis to examine CRS's education-related reports from the 115th Congress to explore what sources are directly and indirectly informing federal policymaking based on references in CRS reports. Findings offer insights into research utilization in the federal education policy process and contribute to the growing literature on intermediary organizations and knowledge brokering.